The basic preconditions for economic education in schools majoring in technology (Pedagogy of Higher and Secondary Education, 2014)
Kulishov V. S. The basic preconditions for economic education in schools majoring in technology.The article highlights the basic preconditions as well as substantiates the great importance of creating the system of economic education in schools majoring in technology.
Keywords: economic education; project and technological activity of schooldren; sustainable development; synergy; major in economics